Simultaneous chronic seneciosis and eurytrematosis in a cow/ Simultânea seneciose crônica e euritrematose em uma vaca - Ighor Augusto de Almeida; Dieggo Ricardo Meira da Silva; Diogini Albano Gomes; João Paulo Elsen Saut; Selwyn Arlington Headley; Luiz Antonio Sangioni (Semina: Ciências Agrárias, 2004)
Chronic intoxication associated with the ingestion of Senecio brasiliensis with concomitant interstitial and periductal pancreatitis induced by Eurytrema spp are described in a cow that demonstrated severe progressive emaciation as its principal clinical manifestation. In chronic seneciosis there was severe toxic hepatitis characterized by periportal and bridging fibrosis, megalocytosis, and proliferation of epithelial bile duct cells. Infestation by Eurytrema spp produced marked periductal and interstitial fibrosis associated with parasitic forms within interlobular pancreatic ducts. Descreve-se a intoxicação crônica por Senecio brasiliensis com concomitante pancreatite intersticial e periductal por Eurytrema spp em uma vaca que demonstrou emagrecimento progressivo como sua principal manifestação clínica. Na intoxicação crônica por Senecio spp observou-se hepatite tóxica caracterizada por fibrose periportal e em ponte, megalocitose e proliferação das células epiteliais dos ductos biliares. A infestação por Eurytrema spp induziu fibrose periductal e intersticial acentuada associada a formas interductais do trematódeo.